If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 6y + 3 = 0 Reorder the terms: 3 + -2x + 6y = 0 Solving 3 + -2x + 6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -2x + -3 + 6y = 0 + -3 Reorder the terms: 3 + -3 + -2x + 6y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2x + 6y = 0 + -3 -2x + 6y = 0 + -3 Combine like terms: 0 + -3 = -3 -2x + 6y = -3 Add '-6y' to each side of the equation. -2x + 6y + -6y = -3 + -6y Combine like terms: 6y + -6y = 0 -2x + 0 = -3 + -6y -2x = -3 + -6y Divide each side by '-2'. x = 1.5 + 3y Simplifying x = 1.5 + 3y
| (y+5)x^1/2=5 | | 3x(x+2)=3x^2+6x | | 8/9p=12/18 | | b+2-(b-2/4)=17/2 | | 32x+41=108 | | 2/9w=24 | | (8p^2+20p+4p^3)/4p^2 | | 24x^2-336x+864=0 | | 200-5X^3+2(3X^2-1)X^2= | | 1/2x^2-9/16=0 | | x^2-36/49=0 | | x^2+2x+15/16=0 | | (5.1)/3 | | -16/19y=-20/38 | | 2+3(x+-5)=5 | | 1/2x^2-1/4x=0 | | 1/1x^2-1/4x=0 | | -8h=-.36 | | -7x-2=-2x-27 | | -.54=.36m | | -4/11y=-16/33 | | -5+3(6+7n)=-29 | | .3v=1.35 | | 3/7k=12/35 | | 4(4x-2x+5)=8x+20 | | n+n+1+n+2+n+3=130 | | b^3=512 | | n^3=115+2n | | x^3-x=60 | | 105+.15m=117.15 | | (x+1)(x-1)(x-6)=0 | | 2(f+3)-2=8+f |